2022
DOI: 10.1055/s-0042-1759878
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Extubations in Pediatric Critical Care: A Case–Control Study

Abstract: The aim of this study was to quantify associations between the risk of unplanned extubation and patient-, environment-, and care-related factors in pediatric critical care and to compare outcomes between children who did and did not experience an unplanned extubation. This is a retrospective case–control analysis including patients <18 years who experienced an unplanned extubation during intensive care unit (ICU) admission (2004–2014). Cases were matched by age, duration of mechanical ventilation, and date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The authors found on modeling that there were two associated explanatory factors: tube-related security and (in)adequacy of patient sedation. In 2022, the journal published a United States Virtual Pediatric Systems (LLC) database study of over 5,700 unplanned extubations in 149 PICUs (2012-2020) and explored associations with the need for reintubation (10). Patients with cardiovascular disease accounted for 14% of the population, but there was no subanalysis of this group.…”
Section: What About Unplanned Extubations In Cicu Patients?mentioning
confidence: 99%
“…The authors found on modeling that there were two associated explanatory factors: tube-related security and (in)adequacy of patient sedation. In 2022, the journal published a United States Virtual Pediatric Systems (LLC) database study of over 5,700 unplanned extubations in 149 PICUs (2012-2020) and explored associations with the need for reintubation (10). Patients with cardiovascular disease accounted for 14% of the population, but there was no subanalysis of this group.…”
Section: What About Unplanned Extubations In Cicu Patients?mentioning
confidence: 99%